Decrease of anti-cyclic citrullinated peptide antibodies and rheumatoid factor following anti-TNFα therapy (infliximab) in rheumatoid arthritis is associated with clinical improvement. Issue 10 (10th September 2004) - Alessandri, C; Bombardieri, M; Papa, N; Cinquini, M; Magrini, L; Tincani, A; Valesini, G
Abstract : Objective: To investigate the effect of infliximab treatment on anti-cyclic citrullinated peptide antibodies (anti-CCP) and rheumatoid factor (RF) in patients with rheumatoid arthritis. Methods: 43 patients with rheumatoid arthritis not responding to disease modifying anti-rheumatic drugs (DMARD) received intravenous infliximab at a dose of 3 mg/kg at baseline and after two and six weeks, and subsequently bimonthly, in combination with methotrexate. Serum samples were collected at baseline and at week 24. A commercial enzyme linked immunosorbent assay was used to test for anti-CCP antibodies; RF were detected using a quantitative nephelometric assay. Results: At baseline, 38 of the 43 patients (88%) were positive for anti-CCP antibodies, and 41 (95%) were positive for RF. The serum titre of anti-CCP and RF decreased significantly after six months of treatment (p = 0.0001 and p<0.0001, respectively). When the patients were grouped on the basis of their clinical response to infliximab, a significant decrease in serum anti-CCP antibodies and RF was observed only in patients who had clinical improvement (ACR 20 and ACR 50). Conclusions: Anti-TNFα treatment in rheumatoid arthritis results in a decrease in the serum titres of RF and anti-CCP antibodies in patients showing clinical improvement, suggesting that these measurements may be a useful adjunct in assessing treatment efficacy.